Challenges were faced during radiography of pregnant women - Arfat, M.; Beg, Tarana; Haq , Afifa (International Journal Of Community Medicine And Public Health, 2024)
Radiography of pregnant patients poses significant challenges to radiographers due to the need to balance diagnostic requirements with the safety of the developing foetus. This article explores the challenges faced by radiographers when conducting radiographic procedures on pregnant women and their foetus and discusses strategies employed to minimize radiation exposure. Key challenges include the risk of foetal radiation exposure, timing of examination, proper positioning of the patient and patient anxiety. Strategies such as radiation shielding, collimation, low-dose techniques and alternative imaging modalities are crucial for minimizing radiation exposure while obtaining diagnostic information. Clear communication between radiographers and patient is essential to ensure the safety and well-being of both the mother and the foetus during radiographic procedure. Radiographers knows the dangers of radiation exposure to fetal health. Now days, diagnostic imaging of pregnant women is increasing. X-ray risks depending on the gestational age of the pregnancy, and other potential health effects. In addition, ethical issues have been considered by improving overall communication to minimize unnecessary radiation exposure to pregnant women and fetuses.